Ocean heat uptake: drivers, variability and impacts - Aengenheyster, M (2022)
Attributions of causes in the fully coupled atmosphere-ocean system are difficult due to a wide range of interactions in the climate system. One way to address this is to break down the fully coupled closed system into two open systems. Such studies often depend on the specification of sea surface temperature to link ocean and atmosphere. Instead, in this thesis we focus on understanding the impacts of perturbations to surface heat fluxes as this gives a better handle on imposing changing processes and improves the realism of air-sea interactions.